Characterization Roasting Level of Arabica Coffee (Coffea arabica) Komasti and Andungsari - Priantari, Ika; Dharmawan, Andi (Jurnal Biologi Universitas Andalas, 2022)
Coffee is one of the drinks that are often consumed by the public Indonesia. Indonesian Coffee and Cacao Research Institute (ICCRI) is a national coffee and cocoa research and development institution has 2 superior Arabica coffee seeds, namely Andungsari 2K Arabica Coffee and Komasti (Andungsari 3 Composite). In general, the sequence of dry processing of coffee cherries includes fruit picking, fruit sorting, fruit drying, pulping and hulling. Next is the roasting process before it becomes coffee grounds. The roasting process converts unsavory raw coffee beans into a drink with a delicious aroma and taste. The perfection of coffee roasting is influenced by 2 factors, namely heat and time, equipment and tools roasting and quality of coffee beans. From the results of treatments 2, 4, 6, 8, 10, 12, 14, 16 and 18 minutes, coffee with city roast criteria was produced in the 7th treatment, namely 14 minutes, with the first crack at 11.30 minutes at 154 Â°C, the color of the beans dark chocolate, has the most popular taste. For treatment 8 (14 minutes) and 9 (18 minutes) the color is more black, oily and smokey, the taste is more espresso. The roasting equipment used is in the dark roast category at a temperature of 170-195 Â°C.